Familial dysalbuminaemic hyperthyroxinaemia interferes with current free thyroid hormone immunoassay methods. Issue 6 (June 2020) - Khoo, Serena; Lyons, Greta; McGowan, Anne; Gurnell, Mark; Oddy, Susan; Visser, W Edward; van den Berg, Sjoerd; Halsall, David; Taylor, Kevin; Chatterjee, Krishna; Moran, Carla
Abstract : Objective: Familial dysalbuminaemic hyperthyroxinaemia (FDH), most commonly due to an Arginine to Histidine mutation at residue 218 (R218H) in the albumin gene, causes artefactual elevation of free thyroid hormones in euthyroid individuals. We have evaluated the susceptibility of most current free thyroid hormone immunoassay methods used in the United Kingdom, Europe and Far East to interference by R218H FDH. Methods: Different, one- and two-step immunoassay methods were tested, measuring free T4 (FT4) and free T3 (FT3) in 37 individuals with genetically proven R218H FDH. Results: With the exception of Ortho VITROS, FT4 measurements were raised in all assays, with greatest to lowest susceptibility to interference being Beckman ACCESS > Roche ELECSYS > FUJIREBIO Lumipulse > Siemens CENTAUR > Abbott ARCHITECT > Perkin-Elmer DELFIA. Five different assays recorded high FT3 levels, with the Siemens CENTAUR method measuring high FT3 values in up to 30% of cases. However, depending on the assay method, FT4 measurements were unexpectedly normal in some, genetically confirmed, affected relatives of index FDH cases. Conclusions: All FT4 immunoassays evaluated are prone to interference by R218H FDH, with their varying susceptibility not being related to assay architecture but likely due to differing assay conditions or buffer composition. Added susceptibility of many FT3 assays to measurement interference, resulting in high FT4 and FT3 with non-suppressed TSH levels, raises the possibility of R218H FDH being misdiagnosed as resistance to thyroid hormone beta or TSH-secreting pituitary tumour, potentially leading to unnecessary investigation and inappropriate treatment.